Pengaruh Literasi Keuangan, Pendidikan dan Pendapatan Terhadap Perilaku Keuangan Usaha Mikro Kecil (UMK) di Kabupaten Gresik - Ilham, Zamani Yahya; Suriyanto, Moh. Agung; Akhiruddin, Anita (Jurnal Sains dan Teknologi, 2023)
Abstract− This study aims to determine the effect of financial literacy, education and income on financial behavior in small micro enterprises (UMK) in Gresik Regency. The data is presented in quantitative form by testing and analyzing the data by calculating the numbers and then drawing conclusions with the test. In this study, the objects studied were all micro and small enterprises (UMK) in Gresik Regency, totaling 223,815 business actors, as well as sampling using the slovin formula with a significance level of 5%, totaling 400 respondents. The results showed that the independent variables of financial literacy, education and income partially had a positive and significant effect on the financial behavior of small micro enterprises (UMK) in Gresik Regency with a significance value below 0.05.